Controlabilidade exata local para as trajetórias de um sistema não-linear acoplado. - Souza, Diego Araujo de (2010)
This dissertation is devoted to prove the local exact controllability to the trajectories for a coupled system, of the Boussinesq kind. In the state system, the unknowns are the velocity field and pressure of the uid (y; p), the temperature (-) and an additional variable c that can be viewed as the concentration of a contaminant solute. We prove several results, that essentially show that it is sufficient to act locally in space on the equations satisfied by (-) and c. The controllability property of this system will be obtained by means of a Carleman inequality for apropriate system and of a inverse function theorem.